Perennial crop production cycle models: Influence of high yielding varieties and prices - Narayana D (Indian Journal of Natural Rubber Research, 1994)
The adjustments in supply response to demand changes in the case of perennial crops are always with a time-lag because of gestation lags and peculiar yield profiles. This leads to characteristic movement of price which in turn makes for phases of area expansion. In order to test the hypothesis a basic model of supply response is set out which is further extended by incorporating introduction of HYV, replanting and price. The empirical analysis of the model using data on natural rubber for the period 1955-1989 has brought out the validity of the model. The production of natural rubber is characterised by cycles owing to the phases in the expansion of area in response to the cyclical behaviour of prices one leading to the other and feeding on it.
Keywords: High yielding varieties; Natural rubber; Perennial crops; Price